Explosion Teeth Box Promotion Based-Media Model Towards Changing Tooth Brushing Behavior among Primary School Students - Melanie Agis Marludia; Masrifan Djamil; Rasipin Rasipin; Suharyo Hadisaputro; Bedjo Santoso (Alta Dharma Publisher, 2020)
Dental and oral health problems in primary school students are in the high category. This is because efforts to improve the dental health behavior of school children are still not optimal. One effective prevention of these problems through the act of brushing your teeth diligently, thoroughly, and regularly. Proper dental health education is given to primary school students in the form of media packaged by learning while playing. Media promotion explosion teeth box is expected to change the behavior of brushing your child's teeth. The study aimed to develop the suitable and to examine the effect explosion teeth box promotion-based-media model to improve tooth brushing among primary school students. Research and Development (R&D) and product/model trials (quasi-experimental pre-test and post-test design-was applied in this study). The subjects of class III primary school students such as the intervention group and the control group. Experts validated the results of the model design. The results found that the average validation of explosion teeth box experts was 86.66 (very feasible) as a medium for promoting dental health in primary school students shown by the p-value (0.001). This model effectively increased tooth brushing (p=0.001) and decreased the index debris score (p=0.001) compared to the control group. The application of an explosion teeth box, which was carried out for ten days, effectively improved brushing teeth in primary school students compared to the control group